The European and the other - Santos, Rafael Chaves (2013)
The first major Austrian Scientific Expedition to Brazil in early nineteenth century produced, in addition to collecting various species and parts of anthropological and ethnographic collections, many compilations of the experiences of their participants. One of these, Johann Natterer, whose permanence in our land was the most time consuming, could not complete his work in life time, but left hundreds of letters that described his knowledge and his experiences of life in the regions of Brazil. This article analyses his texts, which had not been yet studied in Brazil, as a social practice that seeks to demonstrate through language the Eurocentric ideological character.KEYWORDS: Europeans. Reports. Language. Indians.